Peningkatan Keterampilan Proses IPA Melalui Pendekatan Science, Environment, Technology, and Society (SETS) Di Sekolah Dasar - Ismunayah, Rima; Uswatun, Din Azwar; Nurasiah, Iis; Sutisnawati, Astri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The ability of students' understanding of grade V in Science Learning is still low, because some students still consider science learning difficult, so students need skills that emphasize facts, concepts and processes. So this study aims to improve science process skills through the SETS approach in grade V students of SDN Selabintana Wetan. This SETS approach can generate and improve science process skills which can provide opportunities for students to be directly involved in the learning process. This study uses Classroom Action Research (CAR) where in its implementation it is carried out in two cycles. The subjects of this study were 26 grade V students. Data collection techniques were carried out by observation. The results of the study can be proven by the increase in science process skills shown by students in the results of science learning through the SETS approach, namely in the implementation of the pre-cycle, student completeness was only 33% because all students did not show indicators of process skills, then in the implementation of cycle I, student completeness reached 78% and cycle II, student completeness reached 90%. So it can be concluded that using the SETS approach can improve science process skills in grade V students of SDN Selabintana Wetan.